Antioxidant Activity, Total Phenolic Content and Anti-Tyrosinase Activity of Thai Colored Rice Cultivar Extracts - Pukumpuang, Wipawan; Seansrimon, Jiraporn (Journal of Food Health and Bioenvironmental Science, 2023)
This study aimed to evaluate the antioxidant activity, total phenolic content and tyrosinase inhibitory activity of Thai colored rice. Two different colored rice cultivars (Sew-Dang and Nor-Prae) were extracted using water and 95% ethanol. Antioxidant activities of rice extracts were tested using three different methods: DPPH, ABTS and FRAP. These analyses revealed that ethanolic extracts produced stronger antioxidant activity than water extracts. The ethanolic extract of Nor-Prae rice grains contained 114.12 mg GAE/g extract, 147.55 mg TE/g extract, and 152.44 mg FeSO4/g extract tested by DPPH, ABTS and FRAP assays respectively which were significantly higher than Sew-Dang rice (P<0.05).Total phenolic content was determined using the Folin-Ciocalteu method, and the ethanolic extract had significantly greater levels of phenolics than water extracts (P<0.05). Nor-Prae ethanolic extracts were determined to possess the greatest phenolic content, which was 39.18 mg GAE/g extract, relative to other extracts assessed. Tyrosinase inhibitory activities of rice extracts were determined using the dopachrome microplate method. The greatest tyrosinase inhibitory activity was produced by the ethanolic extract of Nor-Prae rice, which inhibited tyrosinase 24.19%, while all water extracts had no affect on the activity of tyrosinase. In summary, the ethanolic extract of Nor-Prae rice had the strongest antioxidant capacity, greatest total phenolic content and the greatest capacity to inhibit tyrosinase activity. This indicated the potential of colored rice as a source of natural antioxidants and tyrosinase inhibitors, which might be used for further cosmetic or pharmaceutical product development.